Deep processes and magmatic activity of the Volyn-Podolian plate - O. V. Usenko (Геофизический журнал, 2010)
Conditions of formation of basalts of the Volyn-Podolian plate (VPP) have been considered. In Vendian primary melts which were close by their composition to picritic gabbro were differentiated at the depth of 30-35 km during first two stages of activization. The third stage when tuffs of the percalian terrain could be produced is not unambiguously subdivided. If the suggested scheme of the process is realized the result of activization in Vendian will be the cold mantle and basic mantle because the melts produced by the upper (crust) asthenosphere are basalts. For explanation of anomalies of paleotemperatures, special features of composition of hydrothermal solutions it is necessary to assume the existence of one more stage (separate activisation) in the territory of VPP.